Mental Speed Exercises and Their Effect on Some Special Abilities and Punches Speed in Young Boxers - Tawfeq, Abaas; Jalal, Kamal (Journal of Physical Education, 2023)
The research aimed at identifying the effect of mental speed exercises designed by the researchers on some special abilities in young boxers as well as on punches speed. The researchers used the experimental method on (12) boxers aged 15 – 16 years old from Al Shula club. The subjects were divided into two groups according to weights class to conclude that mental exercises group have the best effect on some special abilities and the speed of punches     compared to controlling group. Finally, the researchers recommended the necessity of paying attention to mental speed exercises due to their great effect on improving some special abilities in young boxers as well as their effect on improving punches; speed.